Polyion Hydrogels of Polymeric and Nanofibrous Carboxymethyl Cellulose and Chitosan: Mechanical Characteristics and Potential Use in Environmental Remediation - Taisei Kawate; Yehao Wang; Kayee Chan; Nobuyuki Shibata; Yuya Doi; Yuichi Masubuchi; Anatoly Zinchenko (Gels)
Recently, cellulose and other biomass nanofibers (NFs) have been increasingly utilized in the design of sustainable materials for environmental, biomedical, and other applications. However, the past literature lacks a comparison of the macromolecular and nanofibrous states of biopolymers in various materials, and the advantages and limitations of using nanofibers (NF) instead of conventional polymers are poorly understood. To address this question, hydrogels based on interpolyelectrolyte complexes (IPECs) between carboxymethyl cellulose nanofibers (CMCNFs) and chitosan (CS) were prepared by ele+ctrostatic cross-linking and compared with the hydrogels of carboxymethyl cellulose (CMC) and CS biopolymers. The presence of the rigid CMCNF altered the mechanism of the IPEC assembly and drastically affected the structure of IPEC hydrogels. The swelling ratios of CMCNF-CS hydrogels of ca. 40% were notably lower than the ca. 100–300% swelling of CMC-CS hydrogels. The rheological measurements revealed a higher storage modulus (<semantics>G′</semantics>) of the CMCNF-CS hydrogel, reaching 13.3 kPa compared to only 3.5 kPa measured for the CMC-CS hydrogel. Further comparison of the adsorption characteristics of the CMCNF-CS and CMC-CS hydrogels toward Cu2+, Cd2+, and Hg2+ ions showed the slightly higher adsorption capacity of CMC-CS for Cu2+ but similar adsorption capacities for Cd2+ and Hg2+. The adsorption kinetics obeyed the pseudo-second-order adsorption model in both cases. Overall, while the replacement of CMC with CMCNF in hydrogel does not significantly affect the performance of such systems as adsorbents, CMCNF imparts IPEC hydrogel with higher stiffness and a frequency-independent loss (<semantics>G″</semantics>) modulus and suppresses the hydrogel swelling, so can be beneficial in practical applications that require stable performance under various dynamic conditions.